A Meta-Analysis Detailing Overall Sexual Function and Orgasmic Function in Women Undergoing Midurethral Sling Surgery for Stress Incontinence. Issue 2 (28th March 2017) - Szell, Nicole; Komisaruk, Barry; Goldstein, Sue W.; Qu, Xianggui (Harvey); Shaw, Michael; Goldstein, Irwin
Abstract: Introduction: More than 200, 000 midurethral slings are placed yearly for stress urinary incontinence. Approximately 14% to 20% of women experience worsening sexual function overall after these procedures. We postulated that sling placement injures neural pathways regulating "female prostate" tissue within the anterior vaginal wall. Aim: To perform a meta-analysis for overall sexual function and orgasm using validated questionnaires for transvaginal tape, transobturator tape, and their variants. Methods: Effect sizes of preoperative and postoperative questionnaire scores for overall sexual function and orgasm were calculated. Random-effects models were selected for meta-analyses. Statistical analysis involved determination of the ratio of total heterogeneity to total variability. Main Outcome Measures: Differences of overall sexual and orgasm functions were calculated by subtracting postoperative sling scores from preoperative sling scores. Forest plots of effect sizes were performed. Results: Sixty-seven percent of midurethral sling procedures analyzed showed no change or improvement in overall sexual function postoperatively, whereas 33% of studies analyzed for orgasm function showed improvement after the procedure. For transvaginal tape, mean total sexual function and orgasm postoperative scores were significantly higher than preoperative scores. For transobturator tape, mean total postoperative score was significantly higher than the preoperative score; however, the mean orgasm postoperative score was not significantly higher than the preoperative score, possibly because of variability in transobturator tape data. Conclusion: There is a discrepancy between postoperative sexual satisfaction and orgasmic function after midurethral sling surgery. Although overall sexual function remained the same or improved for most women, orgasmic function in only one third of cases improved overall, with most women experiencing no change or deterioration in orgasmic function. Dissection for, and placement of, the midurethral sling can compromise the neural integrity of the anterior vaginal wall, thereby detrimentally affecting the periurethral prostate tissue that is essential to the orgasmic response. We propose that this surgical procedure can compromise orgasmic function in some women. Szell N, Komisaruk B, Goldstein SW, et al. A Meta-Analysis Detailing Overall Sexual Function and Orgasmic Function in Women Undergoing Midurethral Sling Surgery for Stress Incontinence. Sex Med 2017;5:e84–e93.